2011
DOI: 10.1002/mds.23566
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Small Intestinal Bacterial Overgrowth in Parkinson's Disease

Abstract: Small intestinal bacterial overgrowth is highly prevalent in PD. Gastrointestinal motility abnormalities might explain this association.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
105
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 156 publications
(113 citation statements)
references
References 15 publications
6
105
0
2
Order By: Relevance
“…Gastrointestinal dysfunctions, such as constipation and dysphagia, are commonly reported in PD. Gabrielli et al 39 recently showed that small intestinal bacterial overgrowth was highly prevalent in PD. Therefore, decreases in serum catechol sulfate levels in patients with PD may be attributed to abnormal gut microbiota.…”
Section: Discussionmentioning
confidence: 99%
“…Gastrointestinal dysfunctions, such as constipation and dysphagia, are commonly reported in PD. Gabrielli et al 39 recently showed that small intestinal bacterial overgrowth was highly prevalent in PD. Therefore, decreases in serum catechol sulfate levels in patients with PD may be attributed to abnormal gut microbiota.…”
Section: Discussionmentioning
confidence: 99%
“…66,67,99,100 The prevalence of SIBO is 25.0-54.5% in PD patients compared to 8.3-20.0% in normal controls. The presence of SIBO has been associated with a greater degree of impairment in motor control in PD with fluctuation in levodopa response.…”
Section: Small Intestinal Bacterial Overgrowthmentioning
confidence: 99%
“…Thus, a recent Cochrane review concluded that further studies are required to address the gaps in knowledge regarding the role of HP infection in PD [24], and screening PD patients for HP status has yet to enter routine clinical practice. A role for small intestinal bacterial overgrowth (SIBO) in PD has also been proposed recently [4,5,25]. It is known that SIBO can occur as a sequela of HP infection as well as of gut dysmotility [26].…”
Section: Introductionmentioning
confidence: 99%